Endothelial Dysfunction and Varicose Veins: Emerging Scientific Facts and the Homeopathic Approach (Homoeopathy for All, 2026)
Varicose veins are among the  most common manifestations  of chronic venous disease,  affecting a significant proportion  of adults, particularly women,  older individuals, and those with  prolonged standing occupations.  Conventionally, their development  has been explained majorly through  venous valve incompetence and  mechanical venous hypertension  leading to dilation, tortuosity, and  venous stasis. However, emerging  research suggests that varicose veins  are not merely a structural disorder  of failed valves, but a complex  vascular condition involving  endothelial dysfunction, altered  shear stress, chronic inflammation,  oxidative stress, and extracellular  matrix remodelling.
Keywords: Varicose; veins; common; manifestations; venous; disease